Modulation of bilirubin neurotoxicity by the Abcb1 transporter in the Ugt1-/- lethal mouse model of neonatal hyperbilirubinemia - Bockor, Luka; Bortolussi, Giulia; Vodret, Simone; Iaconcig, Alessandra; Jašprová, Jana; Zelenka, Jaroslav; Vitek, Libor; Tiribelli, Claudio; Muro, Andrés F (Human molecular genetics, 2017)
Moderate neonatal jaundice is the most common clinical condition during newborn life. However, a combination of factors may result in acute hyperbilirubinemia, placing infants at risk of developing bilirubin encephalopathy and death by kernicterus. While most risk factors are known, the mechanisms acting to reduce susceptibility to bilirubin neurotoxicity remain unclear. The presence of modifier genes modulating the risk of developing bilirubin-induced brain damage is increasingly being recognised. The Abcb1 and Abcc1 members of the ABC family of transporters have been suggested to have an active role in exporting unconjugated bilirubin from the central nervous system into plasma. However, their role in reducing the risk of developing neurological damage and death during neonatal development is still unknown.To this end, we mated Abcb1a/b-/- and Abcc1-/- strains with Ugt1-/- mice, which develop severe neonatal hyperbilirubinemia. While about 60% of Ugt1-/- mice survived after temporary phototherapy, all Abcb1a/b-/-/Ugt1-/- mice died before postnatal day 21, showing higher cerebellar levels of unconjugated bilirubin. Interestingly, Abcc1 role appeared to be less important.In the cerebellum of Ugt1-/- mice, hyperbilirubinemia induced the expression of Car and Pxr nuclear receptors, known regulators of genes involved in the genotoxic response.We demonstrated a critical role of Abcb1 in protecting the cerebellum from bilirubin toxicity during neonatal development, the most clinically relevant phase for human babies, providing further understanding of the mechanisms regulating bilirubin neurotoxicity in vivo. Pharmacological treatments aimed to increase Abcb1 and Abcc1 expression, could represent a therapeutic option to reduce the risk of bilirubin neurotoxicity.
Keywords: Hyperbilirubinemia, Neonatal; lidé; Glucuronosyltransferase; P-glykoprotein; Mice, Knockout; novorozenecká hyperbilirubinemie; Animals, Newborn; Neurotoxicity Syndromes; Female; mozeček; Cell Survival; bilirubin; Cerebellum; myši; Humans; Mice; neurotoxické syndromy; Disease Models, Animal; Multidrug Resistance-Associated Proteins; proteiny spojené s mnohočetnou rezistencí k lékům; novorozená zvířata; viabilita buněk; mužské pohlaví; zvířata; ženské pohlaví; Animals; myši knockoutované; Bilirubin; Male; glukuronosyltransferasa; modely nemocí na zvířatech; ATP Binding Cassette Transporter, Subfamily B, Member 1